Problem analysis of geotechnical well drilling in complex environment; IOP Conference Series: Earth and Environmental Science; Vol. 24 : Scientific and Technical Challenges in the Well Drilling Progress, 24–27 November 2014, Tomsk, Russia - Kasenov A. K.; Biletskiy M. T.; Ratov B. T.; Korotchenko T. V. Tatiana Valerievna (2015, 2015)
Title screen